Revisão sistemática sobre feridas e curativos e produção de material instrutivo na atenção básica - Ovelar, Sheila Renata Roa (2023)
The present work aims to collect and analyze data from the bibliography and scientific works based on evidence, about the theme wounds and dressings with an emphasis on primary care, after raising the theory, a pedagogical material was made in the format of an instructional manual made available through digital means . It is therefore a descriptive study with a qualitative approach, with a bibliographical review and data collection that took place in existing literature such as books, theses, manuals and articles made available by the Ministry of Health and databases such as: LILACS, SciELO, Capes, MEDLINE, BVS journal portal, among others. The perspective of the research is to contribute to the daily life of multidisciplinary health teams, in terms of care for the public with skin lesions, providing the health team with a clear and objective manual that addresses the main types of wounds and some options for therapeutic treatment.